Methods of DNa methylation analysis:possibilities and limitations of their application in oncology - N. A. Skryabin; A. A. Kashevarova; E. V. Denisov; I. N. Lebedev (Сибирский онкологический журнал, 2016)
Abnormalities of DNA methylation play a significant role in initiation and progression of tumors. In this regard it is necessary to study these aberrations in order to better understand the malignant transformation pathogenesis. For this purpose the adequate and objective methods are required. The principles and possibilities of application of basic methods of DNA methylation analysis are reviewed in the paper